Kupka, Gutfreund & C. : in the National Gallery in Prague - Works by Jiri Kotalik. - Kotalik, Jiri; Galleria Nazionale di Praga; Biennale di Venezia, 1980 (Venezia : La Biennale di Venezia, 1980)
Benda, Bretislav ; Benes, Vincenc ; Braque, Georges ; Capek, Josef ; Derain, André ; Dvorak, Karel ; Filia, Emil ; Guttfreund, Otto ; Jirikovsky, Josef ; Kotrba, Karel ; Kubista, Bohumil ; Kupka, Frantisek ; Lauda, Jan ; Lidincky, Karel ; Makovsky, Vincenc ; Picasso, Pablo ; etc.
La Biennale di Venezia, 01.06 - 28.09.1980
Engels & Italiaans
kunstcatalogus